The Effectiveness of Local Wisdom–Based Islamic Religious Education Learning Strategies - Ramedlon Ramedlon; Damas Ahmad Yunus; Afindi Afindi; Muhammad Mujtaba Asad (Idarah (Jurnal Pendidikan dan Kependidikan), 2024)
Cultural acculturation provides a discourse for strategic renewal to enhance the effectiveness of the teaching of Islamic Religious Education (PAI). This study aims to identify a strategic model of PAI teaching at MAN 1 Bengkulu City by positioning local wisdom as a source of relevant values to strengthen students' understanding and character formation. The research employs a qualitative, descriptive survey approach. Key informants include PAI teachers, students, the school principal, and local customary leaders or cultural experts. Data were collected through in-depth interviews, observations, and document analysis, and then analyzed thematically. The study identified local wisdom values such as togetherness, deliberation, mutual cooperation, and respect for parents as being strongly aligned with Islamic moral principles. The integration of these values was achieved through the selection of effective cultural practices as learning media, modification of learning activities, and provision of space for student reflection. Contextual learning strategies oriented toward cognitive achievement were implemented using Project-Based Learning and Problem-Based Learning methods. Meanwhile, in-depth character formation encourages students to develop an Islamic identity that harmonizes with local culture. The study suggests that integrating local culture offers a new direction for Islamic Religious Education (PAI), making it more relevant to contemporary social and cultural challenges.